Kangaroo mother care: a systematic review of barriers and enablers - Chan, Grace J (Bull World Health Organ, 2016)
OBJECTIVE: To investigate factors influencing the adoption of kangaroo mother care in different contexts. METHODS: We searched PubMed, Embase, Scopus, Web of Science and the World Health Organization’s regional databases, for studies on “kangaroo mother care” or “kangaroo care” or “skin-to-skin care” from 1 January 1960 to 19 August 2015, without language restrictions. We included programmatic reports and hand-searched references of published reviews and articles. Two independent reviewers screened articles and extracted data on carers, health system characteristics and contextual factors. We developed a conceptual model to analyse the integration of kangaroo mother care in health systems. FINDINGS: We screened 2875 studies and included 112 studies that contained qualitative data on implementation. Kangaroo mother care was applied in different ways in different contexts. The studies show that there are several barriers to implementing kangaroo mother care, including the need for time, social support, medical care and family acceptance. Barriers within health systems included organization, financing and service delivery. In the broad context, cultural norms influenced perceptions and the success of adoption. CONCLUSION: Kangaroo mother care is a complex intervention that is behaviour driven and includes multiple elements. Success of implementation requires high user engagement and stakeholder involvement. Future research includes designing and testing models of specific interventions to improve uptake.